모의 수출 ‘후지’ 사과의 품질에 미치는 수확후 1-MCP 처리 및 CA저장 효과 - 박윤문(Youn-Moon Park); 박효근(Hyo Geun Park); 임병선(Byung-Sun Lim) (Weon'ye gwahag gi'sulji, 2011)
Effects of 1-methylcyclopropene (1-MCP) treatment and controlled atmosphere (CA) storage was analyzed for the export quality of 'Fuji' apples after 8-month storage. Apples were harvested from two orchards located in different regions at relatively late stage of maturity for long-term storage. Fruit were treated with 1 ${μ}L{·}L^{-1}$ 1-MCP and then stored in $0^{°}C$ air or CA with 1.5 kPa $O_2$ and < 1.0 kPa $CO_2$ for 8 months. To simulate poststorage export process such as 2-week refrigerated container shipment plus 7-day local distribution, fruit were put in $0^{°}C$ air storage for additional two weeks and then on the shelf for 7 days at $20^{°}C$. Both the 1-MCP treatment and CA storage reduced respiration and ethylene evolution after storage and shipping simulation, and successfully maintained titratable acidity and flesh firmness even after the export process. In 'Fuji' apples harvested after adequate stage of maturity for long-term storage, however, 1-MCP treatment alone seemed not to be satisfactory for the maintenance of sensorial fruit texture for export market. CA storage or 1-MCP treatment/CA storage combination program should be applied for lately harvested 'Fuji' apples exported after eight months storage. '후지' 사과의 8개월 장기저장 후 모의수출과정에서 품질에 미치는 수확 후 1-MCP 처리와 CA저장의 효과를 분석하였다. 장기저장용 성숙기로는 다소 늦은 10월 29일에 청원지역과 안동지역 두 과수원에서 수확한 사과를 $1μL{·}L^{-1}$ 1-MCP 처리를 한 후 8개월 간 $0^{°}C$ 저온저장과 controlled atmosphere(CA) 저장을 수행하였다. 저장 후 2주 저온 컨테이너 운송과 현지유통 7일로 설정한 수출과정은 추가적인 2주 저온저장과 $20^{°}C$ 실온보관 방식으로 모의하였다. 1-MCP 처리 및 CA저장은 저장 및 모의운송 후 호흡과 에틸렌 발생을 억제하였고 모의 수출과정 후까지 적정 산도와 과육경도 유지에 뚜렷한 효과를 보였다. 그러나 장기저장에 적합한 성숙단계를 지나 수확한 사과의 경우, 1-MCP 처리만으로는 수출 시장에서 소비자 관능을 만족시키는 조직감 유지에 충분한 효과를 거두기 어려운 것으로 평가되었다. 본 연구 결과, 수확 시기가 지연되는 '후지' 사과의 8개월 이상 장기저장 후까지 수출 품질을 유지하기 위해서는 CA저장 혹은 1-MCP 처리/CA저장 병용 프로그램 적용의 필요성이 제시되었다